Mutation analysis of the EGFR gene and its downstream signaling pathway in thymic carcinoma patients from a Chinese Han population. (20th October 2016) - Zhan, Ping; Chen, Xiao; Wu, Xiao‐Yuan; Hou, Zhi‐Bo; Qian, Qian; Zhang, Yu; Zou, Jue; Zhang, Yuan‐Qing; Wan, Ming‐Yue; Wang, Jian‐Dong; Yu, Li‐Ke; Xie, Hai‐yan
Abstract: Introduction: For thymic carcinoma (TC), which is a rare epithelial neoplasm of the thymus gland, median survival with current treatments is only 2 years. Objectives: Mutations in the epidermal growth factor receptor (EGFR) gene or its downstream effectors may cause constitutive activation that leads to cell proliferation and metastases. Thus, molecular profiling is essential for selecting TC patients who may respond to anti‐EGFR therapies. Methods: Genomic DNA was extracted from 61 histological samples of TCs. Real‐time polymerase chain reaction (PCR) and direct sequencing were used to assess the mutations in the EGFR downstream pathway. Results: Gene mutations were identified in seven patients (11.5%). In particular, the identified mutations included four mutations in the KRAS gene, one mutation in the BRAF gene, one mutation in the PIK3CA gene, and only one mutation in the EGFR gene itself. Gene mutations in the EGFR downstream pathway were associated with shorter survival time and were observed to be an independent prognostic factor for TC patients. Conclusion: Mutations in the EGFR downstream pathway are not rare in TCs. These data offer interesting possibilities for the future management of TCs, particularly in the era of new targeted therapies.